2021
DOI: 10.1155/2021/5524925
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicine Constitution Correlated with Ischemic Stroke: A Systematic Review and Meta-Analysis

Abstract: Objective. To investigate the correlation between traditional Chinese medicine (TCM) body constitution and ischemic stroke (IS). Methods. Literature search was conducted in databases including Wanfang database, Chongqing VIP, China National Knowledge Infrastructure, Embase, and PubMed from inception to November 16, 2020. Observational studies evaluating the association between TCM body constitution and IS were included for analysis. The distribution of body constitutional types in IS patients was pooled into m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…37 , 38 The recent study showed among the nine constitution types, qi-deficiency constitution, phlegm-dampness constitution, and blood stasis constitution are the common types, accounting for 25%, 23%, and 17%, respectively, in ischemic stroke patients. 39 The results of this study indicated statistical significance in tongue color bluish, ecchymosis and tongue deviation. The former two belong to blood stasis syndrome, while the latter belongs to wind syndrome.…”
Section: Discussionmentioning
confidence: 53%
“…37 , 38 The recent study showed among the nine constitution types, qi-deficiency constitution, phlegm-dampness constitution, and blood stasis constitution are the common types, accounting for 25%, 23%, and 17%, respectively, in ischemic stroke patients. 39 The results of this study indicated statistical significance in tongue color bluish, ecchymosis and tongue deviation. The former two belong to blood stasis syndrome, while the latter belongs to wind syndrome.…”
Section: Discussionmentioning
confidence: 53%
“…In traditional Chinese medicine (TCM) theory, the main causes of ischemic stroke are Qi deficiency and blood stasis (Zhang et al, 2021b;Zheng et al, 2021). Therefore, the main method for treating Frontiers in Cell and Developmental Biology frontiersin.org an ischemic stroke involves nourishing the Qi and activating the blood circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Constitution in TCM is a relatively integrated and stable intrinsic characteristic of mental state, morphological structure, and physiological function formed by congenital and acquired endowment [19]. According to clinical presentations, TCM constitution could be categorized as nine types: inherited special constitution, balance constitution, blood stasis constitution, damp-heat constitution, yin-deficiency constitution, phlegm-dampness constitution, qi-stagnation constitution, qi-deficiency constitution, and yang-deficiency constitution [20]. Because of the clinical correlation between phlegm-dampness constitution with GLMD, scientific studies of phlegm-dampness constitution have attracted the keen interest of many research groups globally [21].…”
Section: Discussionmentioning
confidence: 99%